Alat Makan dan Minum yang Baik Menurut Pandangan Islam: Studi Takhrij dan Syarah Hadis - Rofi Fauzan Marzuq; Susanti Vera; Fuad Hilmi; Engkos Kosasih (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the prohibition of Muslims eating and drinking in vessels made of gold and silver. This research uses qualitative methods through literature study by applying the takhrij hadith and syarah hadith methods. The data used analysis of contemporary issues in the religious field. The results of this study are found the quality of the hadith about the prohibition of Muslims eating and drinking using containers or vessels made of gold and silver, and the prohibition of using silk cloth with the quality of the hadith up to the degree of authentic hadith according to ijtihad scholars. The prohibition is due to the Jewish habit of using vessels made of gold and silver to eat, besides gold is included in the category of toxic metal elements in our bodies and cannot be digested. This study concludes that in Islam the law of eating and drinking in vessels made of gold or silver is prohibited.